Advances in Immunotargeted Therapy for Warm Autoimmune Hemolytic Anemia - WANG Qi; CHEN Miao (Xiehe Yixue Zazhi)
Warm autoimmune hemolytic anemia (wAIHA) is an autoimmune disorder mediated by autoantibodies. With an increasing understanding of the immunopathogenesis of wAIHA, significant progress has been made in the development of drugs targeting different components of the immune system. Consequently, these emerging drugs provide more options for the treatment of patients with wAIHA. Anti-B-cell targeted therapies, represented by novel CD20 monoclonal antibodies, Bruton tyrosine kinase (BTK) inhibitors, phosphatidylinositol 3-kinases(PI3K) inhibitors, and B-cell activating factor of the TNF family (BAFF) inhibitors, have shown remarkable efficacy. Additionally, anti-plasma cell targeted therapies, exemplified by proteasome inhibitors and CD38 monoclonal antibodies, have also demonstrated significant outcomes. Furthermore, advances have been achieved in complement inhibitors, neonatal Fc receptor (FcRn) monoclonal antibodies, spleen tyrosine kinase (SYK) inhibitors, and mammalian target of rapamycin (mTOR) inhibitors. This article reviews the recent advances in immunotargeted therapy for wAIHA, aiming to provide a reference for clinical practice.